Ultrasound Devices to Treat Chronic Wounds: The Current Level of Evidence. (December 2020) - Kotronis, Georgios; Vas, Prashanth R. J.
Chronic wounds cause considerable morbidity and utilize significant health care resources. In addition to addressing wound etiology and treating infection, regular debridement is a key component of wound care with a proven ability to accelerate healing. In this regard, a significant innovation in wound care has been the development of ultrasound debridement technology. The purpose of this review is to evaluate the current evidence behind the technology with an emphasis on noncontact low-frequency (NCLF) ultrasound. A number of studies, especially those evaluating NCLF technology, have demonstrated the potential of ultrasound debridement to effectively remove devitalized tissue, control bioburden, alleviate pain, and expedite healing. However, most of the studies are underpowered, involve heterogeneous ulcer types, and demonstrate significant methodological limitations making comparison between studies difficult; there is a paucity of data on cost-effectiveness. Future clinical trials on ultrasound debridement technology must address the design issues prevalent in current studies, and report on clinically relevant endpoints before adoption into best-practice algorithms can be recommended.